2016
DOI: 10.1097/sap.0000000000000747
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nerve Transfers for Restoration of Shoulder Function After Brachial Plexus Avulsion Injury

Abstract: The purpose of this study was to investigate the effectiveness of shoulder function restoration by dual nerve transfers, spinal accessory nerve to the suprascapular nerve and 2 intercostal nerves to the anterior branch of the axillary nerve, in patients with shoulder paralysis that resulted from brachial plexus avulsion injury. It was a retrospective analysis to assess the impact of a variety of factors on reanimation of shoulder functions with dual nerve transfers. A total of 19 patients were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In studies that investigated DNT procedures, the mean recovery of ≥M4 shoulder abduction ranged from 30% to 88.9%, 10 , 13 , 14 , 15 , 18 and the mean ROM ranged from 92º to 115º. 11 , 12 , 13 , 14 , 15 , 16 , 17 The mean recovery of ≥M4 external rotation ranged from 20% to 60%, with a mean ROM ranging from 54º to 136º. 11 , 12 , 13 , 14 , 15 , 16 , 17 In this case series, the results of the DNT for shoulder abduction were similar to published literature, reaching a mean of 99º with 69% of patients experiencing recovery ≥M4 and a mean of 69º of external rotation with 52% of patients having ≥M4 recovery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In studies that investigated DNT procedures, the mean recovery of ≥M4 shoulder abduction ranged from 30% to 88.9%, 10 , 13 , 14 , 15 , 18 and the mean ROM ranged from 92º to 115º. 11 , 12 , 13 , 14 , 15 , 16 , 17 The mean recovery of ≥M4 external rotation ranged from 20% to 60%, with a mean ROM ranging from 54º to 136º. 11 , 12 , 13 , 14 , 15 , 16 , 17 In this case series, the results of the DNT for shoulder abduction were similar to published literature, reaching a mean of 99º with 69% of patients experiencing recovery ≥M4 and a mean of 69º of external rotation with 52% of patients having ≥M4 recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al 12 reported in their DNT series that patients with longer than 24 months of follow-up and a surgical delay of <3 months had a significantly greater ROM for shoulder abduction but not for external rotation. They also reported a significantly greater ROM for shoulder abduction and external rotation for patients in the ≤30-year-old age group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16,19 Double-and triple-nerve transfers also have been widely used with various combinations of recipients and donors with or without nerve grafts. [2][3][4]6 In this study, we investigated the results of shoulder abduction and ER in patients after single-nerve repair of the upper trunk versus those in patients after dual-nerve repair of the upper trunk and the suprascapular nerve.…”
mentioning
confidence: 99%